2010
DOI: 10.1371/journal.pone.0008611
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell-Derived Factor-1/CXCL12 Contributes to MMTV-Wnt1 Tumor Growth Involving Gr1+CD11b+ Cells

Abstract: BackgroundHistological examinations of MMTV-Wnt1 tumors reveal drastic differences in the tumor vasculature when compared to MMTV-Her2 tumors. However, these differences have not been formally described, nor have any angiogenic factors been implicated to be involved in the Wnt1 tumors.Methodology/Principal FindingsHere, we show that MMTV-Wnt1 tumors were more vascularized than MMTV-Her2 tumors, and this correlated with significantly higher expression of a CXC chemokine, stromal cell-derived factor-1 (SDF1/CXCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
(43 reference statements)
2
21
0
Order By: Relevance
“…Mainly, we isolated CD45 þ hematopoietic and CD45 À stroma cells and 2 distinct tumor epithelial cells referred to as basal/myoepithelial and luminal cells. Sorted epithelial cells have been characterized by the expression of cytokeratin isotypes (CK5 for basal/myoepithelial cells and CK18 for luminal epithelial cells) and basal/myoepithelial cell marker, P-cadherin and smooth muscle actin (2). By examining the transcripts from these isolated cell populations, we found that IGF-I was predominantly expressed by the tumor hematopoietic cells (CD45 þ ), and IGF-II was expressed by the CD45 À fibroblasts enriched stromal cells (Fig.…”
Section: Paracrine Effect Of Igf and Wnt Signaling In Wnt1 Tumorsmentioning
confidence: 98%
See 3 more Smart Citations
“…Mainly, we isolated CD45 þ hematopoietic and CD45 À stroma cells and 2 distinct tumor epithelial cells referred to as basal/myoepithelial and luminal cells. Sorted epithelial cells have been characterized by the expression of cytokeratin isotypes (CK5 for basal/myoepithelial cells and CK18 for luminal epithelial cells) and basal/myoepithelial cell marker, P-cadherin and smooth muscle actin (2). By examining the transcripts from these isolated cell populations, we found that IGF-I was predominantly expressed by the tumor hematopoietic cells (CD45 þ ), and IGF-II was expressed by the CD45 À fibroblasts enriched stromal cells (Fig.…”
Section: Paracrine Effect Of Igf and Wnt Signaling In Wnt1 Tumorsmentioning
confidence: 98%
“…Immunofluorescence staining was conducted on formalinfixed paraffin-embedded tumor sections (2). For image analysis, SlideBook software was used to measure pixel intensities and calculated as previously described (16).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Whole tumors were minced into small pieces, followed by sequential digestion with Media I for 60 minutes and Media II for 15 minutes, as previously described (22). Single cells were first incubated at room temperature for 10 minutes with rat anti-mouse CD16/CD32 mAb (Fc block; BD Biosciences), followed by staining with the following fluorophore-conjugated antibodies: anti-CD11b (integrin aM chain, Mac-1, a-chain, M1/70; BD Pharmingen), anti-Ly6G (Gr1, RB6-8C5; eBioscience), anti-CD31 (PECAM-1; eBioscience), anti-human/mouse CXCR7 (8F11-M16; BioLegend), anti-F4/80 (BM8; eBioscience), and anti-CXCR4 (CD184; BioLegend).…”
Section: Facs Analysismentioning
confidence: 99%